Hot subdwarf stars in the Galactic halo Tracers of prominent events in late stellar evolution - Geier, Stephan; Kupfer, Thomas; Schaffenroth, Veronika; Heber, Ulrich (2016)
Hot subdwarf stars (sdO/Bs) are the stripped cores of red giants located at the bluest extension of the horizontal branch. They constitute the dominant population of UV-bright stars in old stellar environments and are most likely formed by binary interactions. We perform the first systematic, spectroscopic analysis of a sample of those stars in the Galactic halo based on data from SDSS. In the course of this project we discovered 177 close binary candidates. A significant fraction of the sdB binaries turned out to have close substellar companions, which shows that brown dwarfs and planets can significantly influence late stellar evolution. Close hot subdwarf binaries with massive white dwarf companions on the other hand are good candidates for the progenitors of type Ia supernovae. We discovered a hypervelocity star, which not only turned out to be the fastest unbound star known in our Galaxy, but also the surviving companion of such a supernova explosion.
Keywords: binaries: spectroscopic; binaries: eclipsing; stars: subdwarfs; stars: brown dwarfs